The Great Pearl Secret - Williamson, C. N. (Charles Norris), 1859-1920; Williamson, A. M. (Alice Muriel), 1869-1933; De Miskey, Julian, 1898-1976 (Salt Lake City, UT : Project Gutenberg, 2018)
"The Great Pearl Secret" by C. N. Williamson and A. M. Williamson is a novel likely written in the early 20th century. The story unfolds around Juliet Phayre, an American heiress engaged to the Duke of Claremanagh, as she navigates the complexities of love, jealousy, and secrets surrounding a famous set of pearls rumored to belong to a Tsarina. The opening chapters introduce a setting filled with social expectations and a web of relationships that hint at underlying tensions. The opening of the narrative begins in the luxurious surroundings of Harridge s Hotel, where Juliet's friends and family discuss wedding preparations and the anticipated arrival of the Tsarina pearls. Juliet exhibits charming innocence alongside her social status, yet a sense of insecurity about her fiancé's past flirtations with the enigmatic dancer Lyda Pavoya permeates her interactions. Captured in the dynamic conversations between characters, the complexities of relationships are hinted at, especially as Juliet grapples with her love for Claremanagh while facing whispers of betrayal. As the story progresses, it becomes apparent that the pearls hold secrets that might unravel more than just a wedding. (This is an automatically generated summary.)
Release date is 2018-01-31
Produced by Al Haines
Keywords: Detective and mystery stories; Jewelry theft -- Fiction